DEVELOPMENT OF THE MIDDLE EAST SCIENCE AND EDUCATION SYSTEM - Rosyidah Azzahra (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
The Islamic education systems in the Middle East have passed numerous phases, starting from the time of Rasulullah until the power of Turk Usmani. Due to the development of science and technology, this study aims to formulate Middle East’s education systems. This research uses the type or approach of library research, namely the study of theory, scientific reference, and scientific literature related to the developing norms, values, and culture over a studied social situation. Results of this research show that the implementation of the education system in the countries in the Middle East cannot be separated from the history of Islamic education in its emergence. Until now, these countries, like Iraq, Saudi Arabia, and Egypt, are still adopting education systems focused on Islamic teachings. Saudi Arabia has a particular education in the Islamic field to prepare a clerical council.